2021
DOI: 10.1155/2021/5529792
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Performance and Cavitation Analysis in Bottom Outlets of Dam Using CFD Modelling

Abstract: Bottom outlets are significant structures of dams, which are responsible for controlling the flow rate, operation, or removal of reservoir sedimentation. The service gate controls the outlet flow rate, and whenever this gate is out of order, the emergency gate which is located at upstream is utilized. The cavitation phenomenon is one of the common bottom outlets’ problems due to the rapid flow transfer. The present research is a numerical study of the flow pattern in a dam’s bottom outlet for different gate op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For instance, in the Rance estuary, the pattern of residual flow changed due to the discharge of the La Rance tidal power plant (Kirby and Retière, 2009). Yamini et al (2021) suggested that the vertical residual structure caused by dam discharge can be very considerable in reservoirs depending on the type of sluice structure of the dam. For Jiaozhou Bay, China, Li et al (2014) mentioned an important environmental change as the residual flow velocity decreased at the entrance of the bay after the construction of the bridge and the ability of water exchange also decreased.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the Rance estuary, the pattern of residual flow changed due to the discharge of the La Rance tidal power plant (Kirby and Retière, 2009). Yamini et al (2021) suggested that the vertical residual structure caused by dam discharge can be very considerable in reservoirs depending on the type of sluice structure of the dam. For Jiaozhou Bay, China, Li et al (2014) mentioned an important environmental change as the residual flow velocity decreased at the entrance of the bay after the construction of the bridge and the ability of water exchange also decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Co mputational Flu id Dynamic (CFD) is a suitable tool to investigate many engineering problems, e.g. aerodynamic [1], cavitation [2], hydraulic [3,4], energy systems [5,6], heat transfer [7,8], mu ltiphase flow [9][10][11]. Today, two-phase ejectors are highly efficient and widely applied in various industries.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, they investigated various nonlinear equations by maple software. Aminoroayaie Yamini et al [32] Mousavimehr et al [33] Kostikov and Romanenkov [34] have examined the following issues. The first issue was the CFD model to investigate the hydraulic performance of the hole in the dam.…”
Section: Introductionmentioning
confidence: 99%